The art and myth of organic agriculture for nature conservation and sustainable food production: perspective of Bangladesh - Sarker, M. A. (International Journal of Agricultural Technology, 2021)
Bangladesh has really plenty of opportunities to promote organic agriculture in producing safe food for its huge malnourished population and maintain the sustainability of agricultural systems as well as conserve the nature. Moreover, due to having pro-poor attributes, organic agriculture of Bangladesh can provide better income for the smallholder organic growers through lowering production costs and ensuring premium prices. However, public sector research and extension agencies need to have some massive programme to remove farmers’ confusion and link organic farmers with market. In addition, Ministry of Agriculture and Ministry of Commerce need to work jointly for introducing certification for organic produces that might create quicker access of Bangladesh’s organic produces in global organic market that will ultimately contribute in national economy and wide spread rural poverty reduction through export earnings